2014
DOI: 10.1209/0295-5075/107/60004
|View full text |Cite
|
Sign up to set email alerts
|

Energy flow between two hydrodynamically coupled particles kept at different effective temperatures

Abstract: We measure the energy exchanged between two hydrodynamically coupled micronsized Brownian particles trapped in water by two optical tweezers. The system is driven out of equilibrium by random forcing the position of one of the two particles. The forced particle behaves as it has an "effective temperature" higher than that of the other bead. This driving modifies the equilibrium variances and cross-correlation functions of the bead positions: we measure an energy flow between the particles and an instantaneous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(98 citation statements)
references
References 36 publications
3
82
0
Order By: Relevance
“…Recent works have shown that exerting random forces on a microscopic particle one can accurately tune the effective kinetic temperature of the particle both under equilibrium [20][21][22] and nonequilibrium driving [23]. However, the application of such a technique to implement nonisothermal processes has not been fully exploited yet [24].…”
mentioning
confidence: 99%
“…Recent works have shown that exerting random forces on a microscopic particle one can accurately tune the effective kinetic temperature of the particle both under equilibrium [20][21][22] and nonequilibrium driving [23]. However, the application of such a technique to implement nonisothermal processes has not been fully exploited yet [24].…”
mentioning
confidence: 99%
“…To investigate this further we now consider the energy transferred between the two microspheres in the system. Energy transfer between hydrodynamically coupled microspheres has previously been considered for the case of two particles held out of equilibrium at different effective temperatures [31]. In our case, the hydrodynamic flow generated by the actuator does work on the optically trapped probe microsphere to move it away from its equilibrium position in the harmonic potential of the stationary optical trap.…”
Section: Energy Transfer Between the Actuator And Probe Microspheresmentioning
confidence: 98%
“…For example, one could be interested in the response to temperature variations of a glassy system undergoing a relaxation process [32,33]. Alternatively, a nonequilibrium steady state may be imposed by putting the system in contact with two reservoirs at different temperatures [34,35]. It is the case of an experiment recently realized with a simple desktop electric circuit in which * baiesi@pd.infn.it † yolcu@pd.infn.it one resistor was kept at room temperature while the other was maintained at a lower temperature [34].…”
Section: Introductionmentioning
confidence: 99%